Validity of the Demirjian Method for Dental Age Estimation in Romanian Children - Abel Emanuel Moca; Gabriela Ciavoi; Bianca Ioana Todor; Bianca Maria Negruțiu; Emilia Albinița Cuc; Raluca Dima; Rahela Tabita Moca; Luminița Ligia Vaida (MDPI AG, 2022)
Dental age assessment is useful in various medical fields. The Demirjian method for dental age estimation is one of the most widely used in the field of pediatric dentistry. The aim of this study was to verify the accuracy of the Demirjian method in determining age in a sample of girls and boys from Oradea, Romania. This retrospective and radiographic study was based on the evaluation of 1006 panoramic radiographs, belonging to 1006 patients (431 boys and 575 girls) with ages between 3 and 13.9 years from the city of Oradea, Romania. They were collected from three private dental practices from Oradea and were analyzed between 1 September 2021, and 10 November 2021. The patients were distributed into 11 age groups, each group spanning over one year (e.g., 3-3.9, 4-4.9). For the assessment of dental age, the Demirjian method was used, which is based on the evaluation of the developmental stages of the lower left permanent teeth. The mean chronological age of the patients was 9.496 ± 2.218 years, and the mean dental age was 10.934 ± 2.585 years. The overestimation of dental age was obtained in all age groups for the entire sample. As such, dental age was higher than chronological age, with values varying from 0.34 years in the 3-3.9 years age group to 1.7 years in the 10-10.9 years age group. In girls, dental age was higher than chronological age, with values varying from 0.46 years in the 3-3.9 years age group to 1.73 years in the 11-11.9 years age group, while in boys, the values varied from 0.15 years in the first age group to 2.02 years in the 10-10.9 years age group. The comparison of the differences between chronological age and dental age according to the gender of the patients revealed that the distribution of the differences was nonparametric in both groups according to the Shapiro-Wilk test (p < 0.05). The differences between the groups were not significant according to the Mann-Whitney U test. However, larger differences were identified for boys (1.46 years) than girls (1.417 years), with an overestimation of the dental age. The Demirjian method overestimated the age of the children included in the investigated sample, with different values for the different age groups investigated, and requires adaptations.